FALSAFAH PANCASILA SEBAGAI LANDASAN PENDIDIKAN DALAM LAYANAN BIMBINGAN DAN KONSELING DI INDONSESIA - Hasrul, Hasrul; Habsyi, Irsan; Makki, M Ismail (Jurnal Pendidikan dan Ekonomi (JUPEK), 2023)
This research aims to find a conceptual explanation regarding Pencasila as a philosophical system and as a basis for education in the implementation of guidance and counseling in Indonesia. The method used is library research which refers to four steps, namely; selecting concepts to be reviewed, reading and analyzing (synthesizing) literature, and writing articles. The results of the conceptual analysis of this study explain that the Pancasila philosophy is closely related to guidance and counseling, because it is by its main essence, namely always prioritizing the principles of comfort and prosperity in living together among fellow humans. Apart from that, Pancasila is also a foundation of education and a basic foundation and framework for guidance and counseling teachers/school counselors in implementing guidance and counseling services in Indonesia. Currently and in the future, guidance and counseling teachers/school counselors and other guidance and counseling practitioners can implement two major issues, namely religious counseling and multicultural counseling which are in line with the essence of the Pancasila philosophy in Indonesia.